2018
DOI: 10.1044/2018_jslhr-s-17-0439
|View full text |Cite
|
Sign up to set email alerts
|

Treating Speech Movement Hypokinesia in Parkinson's Disease: Does Movement Size Matter?

Abstract: Purpose This study evaluates the effects of a novel speech therapy program that uses a verbal cue and gamified augmented visual feedback regarding tongue movements to address articulatory hypokinesia during speech in individuals with Parkinson's disease (PD). Method Five participants with PD participated in an ABA single-subject design study. The treatment aimed to increase tongue movement size using a combination of a verbal cue and augmented visual fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 74 publications
0
18
0
Order By: Relevance
“…The number of sessions for using digital games ranged from 1 37,38 to 4 32,33 per week, and the duration of each session was from 5 24,36 to 45 min. 34,37 The number of sessions was not mentioned in the 2 articles. 31,39 3.9 | Outcome Although the reviewed articles revealed the positive impact of digital games on speech [32][33][34]36,38 and the patients' motivation during the therapy, 24,31,32,37,39 2 articles (20%) mentioned that personalized speech therapy should be considered in designing digital games.…”
Section: Number Of Sessionsmentioning
confidence: 99%
“…The number of sessions for using digital games ranged from 1 37,38 to 4 32,33 per week, and the duration of each session was from 5 24,36 to 45 min. 34,37 The number of sessions was not mentioned in the 2 articles. 31,39 3.9 | Outcome Although the reviewed articles revealed the positive impact of digital games on speech [32][33][34]36,38 and the patients' motivation during the therapy, 24,31,32,37,39 2 articles (20%) mentioned that personalized speech therapy should be considered in designing digital games.…”
Section: Number Of Sessionsmentioning
confidence: 99%
“…Nevertheless, several studies have tested children from five years of age onwards (e.g., Katz & Bharadwaj, 2001;Cheng et al, 2007;Schötz et al, 2013), giving important insights into the development of individual articulators during the process of early speech acquisition. Articulographs have also frequently been used to study disordered speech in individuals suffering from various conditions that can impact speech production and/or speech motor control, ranging from speech disorders such as stuttering and cluttering (Didirkova & Hirsch, 2019;McClean, Tasko, & Runyan, 2004;Hartinger & Mooshammer, 2008) or apraxia or speech (e.g., Bartle-Meyer, Goozée, & Murdoch, 2009;Nijland, Maassen, Hulstijn, & Peters, 2004); hypokinetic dysarthria (e.g., Kearney et al, 2018;Mefferd & Dietrich, 2019) or Amyotrophic Lateral Sclerosis (e.g., Lee & Bell, 2018;Shellikeri et al, 2016) to congenital conditions such as cleft lip (e.g., van Lieshout, Rutjes, & Spauwen, 2002) or congenital blindness (e.g., Trudeau-Fisette, Tiede, & Ménard, 2017). Using EMA to study disordered speech (more studies can be found in the Appendix) is important to provide insight into the underlying issues of speech motor control that cannot be detected through acoustics only.…”
Section: Participantsmentioning
confidence: 99%
“…The reference sensors can alternatively be prepared and placed on a pair of goggles, on the frame of a pair of plastic glasses, or on a headband (e.g., Ji, Berry, & Johnson, 2013;Mefferd, 2019;Thompson & Kim, 2019;Kearney et al, 2018). The Appendix shows additional information regarding individual researchers' strategies to place reference sensors.…”
Section: Preparation and Adhesionmentioning
confidence: 99%
“…It therefore follows that, from a cognitive and motor learning perspective, rehabilitation in PD should aim to foster the re-acquisition of lost habitual, goal-based motor behavior [37]. To achieve this result, clinicians may take advantage of multidisciplinary approaches [26] including physiotherapy, occupational therapy [62], speech and swallowing therapies [63].…”
Section: Motor-cognitive Intervention In Pd: Scientific Rationale and Clinical Evidencementioning
confidence: 99%